Preferences for 'New' Treatments Diminish in the Face of Ambiguity. (12th May 2016) - Harrison, Mark; Marra, Carlo A.; Bansback, Nick
Summary: New products usually offer advantages over existing products, but in health care, most new drugs are 'me‐too', comparable in effectiveness and side effects to existing drugs, but with a more ambiguous evidence base around adverse effects. Despite this, new treatments drive increased health care spending, suggesting a preference for 'newness' in this setting. We explore (1) whether preferences for treatments labeled 'new' exist and (2) persist once the ambiguity in the evidence base reflecting newness is described. We use a Canadian general population sample ( n  = 2837) characterized by their innovativeness in adopting new products in normal markets. We found that innovators/early adopters ( n  = 173) had significant preferences for 'newer' treatments ( B  = 0.162, p  = 0.038) irrespective of comparable benefits and side effects and all respondents had significant preferences for less ambiguity in benefit/side effect estimates. Notably, when 'newness' was combined with ambiguity, no significant preferences for new treatments were observed regardless of respondent innovativeness. We conclude that preferences for new products exist for some people in health care markets but disappear when the implication of ambiguity in the evidence base for new treatments is communicated. Physicians should avoid describing treatments as 'new' or be mindful to qualify the implications of 'new' treatments in terms of evidence ambiguity. Copyright © 2016 John Wiley & Sons, Ltd.